Diversity in Adaptive Evolution of Methicillin-Resistant Staphylococcus aureus Clinical Isolates Under Exposure to Continuous Linezolid Stress in vitro - Han T; Jia T; Wang J (Infection and Drug Resistance)
Tala Han,1 Ting Jia,1 Junrui Wang1,2 1Department of Laboratory Medicine, Affiliated Hospital of Inner Mongolian Medical University, Hohhot, 010050, People’s Republic of China; 2Inner Mongolia Key Laboratory of Clinical Pathogenic Microorganism, The Affiliated Hospital of Inner Mongolian Medical University, Hohhot, 010050, People’s Republic of ChinaCorrespondence: Junrui Wang, Clinical Laboratory, Affiliated hospital of Inner Mongolian Medical University, Hohhot, 010050, People’s Republic of China, Tel +86 04713451315, Email wangjunrui123@yeah.netBackground: Linezolid resistance in methicillin-resistant Staphylococcus aureus (MRSA) was reported frequently in recent years, but the mechanism underlying this process was less reported, especially for clinical isolates with different genetic background. Thus, this study aims to explore the adaptive evolution characteristics underlying linezolid resistance in MRSA clinical isolates exposed to continuous induction stress of linezolid in vitro.Methods: The in vitro susceptibility of 1032 MRSA clinical isolates to linezolid was detected using commercial VITEK-2 equipment via broth microdilution. MRSA isolates with different minimum inhibitory concentration (MIC) values for linezolid were randomly selected to perform the assay of adaptive laboratory evolution with sub-inhibitory concentrations of linezolid. Polymerase chain reaction assays and sequencing techniques were performed to detect well-known molecular determinants related to linezolid resistance, including the expression of optrA and cfr, mutations of 23S rRNA gene and ribosomal protein (L3, L4, L22) encoding genes (rplC, rplD, rplV).Results: After induction with sequentially increasing concentrations of linezolid, all four MRSA strains (L914, L860, L1096, and L2875) evolved into linezolid-resistant strains over various induction times (480, 384, 288, and 240 h) and universally formed small colony variants. A new mutation in the domain V region of 23S rRNA gene (C2404T) and one mutation in amino acid sequences of ribosomal protein (Met208Thr) were firstly identified among linezolid-resistant strains. Except G2576T mutations in 23S rRNA gene, the distribution of other mutations (A2451T, T2504A, C2404T, T2500A, G2447T) exhibited obvious strain heterogeneity. Furthermore, as the MIC to linezolid increased, the copy numbers of point mutations in the V region of 23S rRNA gene increased correspondingly.Conclusion: Strain-specific evolution of resistance to linezolid among MRSA clinical isolates was firstly identified in this study. MRSA isolates with higher MICs for linezolid evolved more easily into resistant ones, which calls for precise monitoring of linezolid resistance levels in patients receiving treatment for MRSA infections with linezolid.Keywords: MRSA, linezolid, inducible resistance, resistance mechanism